2019
DOI: 10.2196/10868
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Insight Into the Challenges of Diagnosing Degenerative Cervical Myelopathy Using Web-Based Symptom Checkers

Abstract: BackgroundDegenerative cervical myelopathy (DCM) is a common debilitating condition resulting from degeneration of the cervical spine. While decompressive surgery can halt disease progression, existing spinal cord damage is often permanent, leaving patients with lifelong disability. Early surgery improves the likelihood of recovery, yet the average time from the onset of symptoms to correct diagnosis is over 2 years. The majority of delays occur initially, before and within primary care, mainly due to a lack o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…Multiple sclerosis (MS), cauda equina syndrome (CES) and diabetes mellitus were selected as the three disease comparators and list of search terms compiled accordingly (table 2). 16–19 MS is a common differential for DCM,20 with overlapping signs and symptoms. While DCM is likely to be more prevalent in reality,1 currently their characterised epidemiology is comparable 21 22.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple sclerosis (MS), cauda equina syndrome (CES) and diabetes mellitus were selected as the three disease comparators and list of search terms compiled accordingly (table 2). 16–19 MS is a common differential for DCM,20 with overlapping signs and symptoms. While DCM is likely to be more prevalent in reality,1 currently their characterised epidemiology is comparable 21 22.…”
Section: Resultsmentioning
confidence: 99%
“…DCM patients were surveyed online and this confirmed that the diagnosis of DCM is frequently delayed 10. The question of whether this is due to lack of knowledge among health professionals and whether this was the consequence of a gap in medical education was formulated with the input of DCM sufferers at the First Cambridge Myelopathy day.…”
Section: Methodsmentioning
confidence: 97%
“…In addition, an increasing number of less well-described symptoms such as dysaesthetic sensory symptoms, 6 chest tightness 20 and headache 21 are being reported. 22 Neurological examination findings include upper motor neuron signs in the upper and lower limbs: spasticity and hyperreflexia in addition to weakness. 1 14 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, an increasing number of less well-described symptoms such as dysaesthetic sensory symptoms, 6 chest tightness 20 and headache 21 are being reported. 22 Neurological examination findings include upper motor neuron signs in the upper and lower limbs: spasticity and hyperreflexia in addition to weakness. 1 14 The latest international guidelines 23 recommend surgical decompression as the only evidence-based management 24 25 for patients with moderate to severe, or progressive DCM.…”
Section: Why Assess Dcm Education?mentioning
confidence: 99%
“…[3][4][5] These domains, for example, are all measured by the modified Japanese Orthopedic Association scale, the international standard on disease severity and reference for treatment decision making. 6 However, there are a number of reports of broader and prevalent disability, 7 including headaches, 8 movement disorders, 9 respiratory dysfunction, 10 and hypertension. 11 A screening tool developed in Japan identified chest pain as predictive of DCM.…”
Section: Introductionmentioning
confidence: 99%